Factors Influencing Academic Performance of English Literature Students - Widyastuti, Susana; Andriyanti, Erna; Nurhayati, Ari (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. Student success is one of key goals of higher education, thus necessary steps are taken to identify how it can be achieved. However, students vary in their ability and performance in completing their studies with various factors attributing to these variations. This study offers identification of the factors within the context of English language program. Examining students’ perception, it attempts to reveal ways in which personal, internal, and external factors and different stages of study may interact to influence student's academic performance. The primary data was a Google Form Questionnaire to 217 students (n=217) of the English literature study program in a state university in Yogyakarta. Through descriptive statistics, the Likert Rating Scale data were analyzed using R. Qualitative data underwent reduction, categorization, and representation using R Qualitative Data Analysis (RQDA). Findings reveal that the Confirmatory Factor Analysis (CFA) satisfied the goodness of fit criterion. The linear regression analysis using the variables from the CFA model revealed that University Learning Facilities, Liking one’s study program, Courses meeting students’ expectations, and Student's Interest in the courses explained 51.31% of the variation (R-squared=0.513) in Students' Academic Performance. However, lecturers negatively impact students’ success, alongside factors like mental health. Further research through in-depth interviews with alumni could establish a more supportive academic system.Keywords: CFA, EFA, student’s academic performance, motivation factors, obstructing factors